2018
DOI: 10.21274/jtm.2018.1.2.167-174
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembelajaran Discovery Learning terhadap Kemampuan Berpikir Kritis Peserta Didik Ditinjau dari Motivasi Belajar

Abstract: Penelitian ini bertujuan untuk mengetahui eksperimentasi model discovery learning dan model pembelajaran langsung terhadap kemampuan berpikir kritis ditinjau dari motivasi belajar peserta didik pada mater segiempat dan segitiga. Metode yang digunakan pada penelitian ini kuantitatif berupa eksperimen semu. Intrumen dalam penelitian ini adalah tes kemampuan berpikir kritis yang disajikan dalam bentuk post-test, kuesioner motivasi belajar dan lembar observasi. Analisis uji hipotesis dalam penelitian ini yaitu uji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Based on the data, discovery learning model assisted by interactive video on experimental group was effective to improve critical thinking skill than control group. Besides that, it is supported by Putri, Mulyanti, and Imswatama (2018) that the use of discovery learning was effective to improve critical thinking skills and motivate students learning the presented materials. It is supported by Martanti and Rusdarti (2019) stating that appropriate learning media selection could be an important matter to ensure the wanted information delivered and understood by students.…”
Section: N-gain Test Of Critical Thinking Skillsmentioning
confidence: 88%
“…Based on the data, discovery learning model assisted by interactive video on experimental group was effective to improve critical thinking skill than control group. Besides that, it is supported by Putri, Mulyanti, and Imswatama (2018) that the use of discovery learning was effective to improve critical thinking skills and motivate students learning the presented materials. It is supported by Martanti and Rusdarti (2019) stating that appropriate learning media selection could be an important matter to ensure the wanted information delivered and understood by students.…”
Section: N-gain Test Of Critical Thinking Skillsmentioning
confidence: 88%
“…These results are in line with research findings [2] regarding the learning model with discovery learning which shows that there is a significant influence on the critical thinking ability score of the experimental class conducted using the learning model which is higher than the control Based on several findings in previous studies that discussed the effect of the discovery learning model this model has a significant effect on critical thinking skills. Research findings by [6] [7] [2] show the results that the model discovery learning supports and has an influence on students' critical thinking skills. However, there has been no research that has found any effect when viewed from the perspective of students' perceptions of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the approach discovery can involve students in independent learning activities, critical thinking, and understanding [2] [21]. In practice, the model discovery learning has several advantages, namely, 1) increasing student experience in learning, 2) providing opportunities for students to be closer to sources of knowledge other than books, 3) exploring student creativity, 4) being able to increase students' self-confidence, and 5) increase cooperation between students [6] [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a gap in the literature connecting the Talking Stick with the development of critical thinking in the context of counselling group sessions. Group counselling combined with the "talking stick" game becomes a potential foundation for addressing the low critical thinking abilities of students (Putri, 2019;Jannah & Wirastania, 2022;Tangahu, 2023).…”
Section: Introductionmentioning
confidence: 99%